A Critical Review Of Ahiputna vyadhi- An Ayurvedic Aspect - Gutakar, Sneha; Sharma, Rukmani (International Research Journal of Ayurveda & Yoga, 2021)
Childhood is considered to be important phase in one’s life. It has different phases that range from reflexes at birth, development milestones (that causes mental and physical development of child) to health problems. Ahiputna is one of the diseases that is common during childhood. It can be correlated with napkin rashes or diaper dermatitis. The skin and mucous membrane around the anal region is very sensitive and delicate during infancy and it takes few months after birth to get barrier function. Improper hygiene can lead to rashes, itching and sometimes ulcer also. Acharyas have mentioned a number of formulations for the disease along with the treatment of stanya dushti as it is a dushta stanayajanan vyadhi. This article comprises of ayurvedic concepts of disease.